On-line marketingová komunikace - Vrátná, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce se zaměřuje na on-line marketingovou komunikaci start-upu Stopskate. V teoretické části jsou představeny a vysvětleny základní pojmy spjaté s on-line marketingovou komunikací, které jsou poté využity v analytické části, jež hodnotí současný stav podniku. Na základě provedených analýz a dotazníkového šetření jsou v návrhové části představeny vlastní návrhy pro zlepšení on-line marketingové komunikace start-upu Stopskate.

The bachelor thesis focuses on the on-line marketing communication of the Stopskate start-up. The theoretical part introduces and explains the basic concepts associated with on-line marketing communication, which are then used in the analytical part, which evaluates the current situation of the company. Based on the performed analyses and questionnaire survey, own proposals for improving the on-line marketing communication of the Stopskate start-up are then presented.
On-line marketing communication
Keywords: on-line marketingová komunikace; marketingový mix; komunikační mix; dotazníkové šetření; reklamní kampaň; on-line marketing communication; marketing mix; communication mix; questionnaire survey; advertising campaign